Synergistic antibacterial effects of ultrasound combined nanoparticles encapsulated with cellulase and levofloxacin on Bacillus Calmette-Guérin biofilms - Zhang, Zhifei; Zhang, Yuqing; Yang, Min; Hu, Can; Liao, Hongjian; Li, Dairong; Du, Yonghong (Frontiers in Microbiology, 2023)
Tuberculosis is a chronic infectious disease. The formation of cellulose-containing biofilms by Mycobacterium tuberculosis (MTB) poses a great challenge for the treatment of tuberculosis. Herein, a composite nanoparticles loaded with cellulase (CL) and levofloxacin (LEV) (CL@LEV-NPs) was fabricated and then combined with ultrasound (US) irradiation to promote chemotherapy and sonodynamic antimicrobial on Bacillus Calmette-Guérin bacteria (BCG, a mode of MTB) biofilms. The CL@LEV-NPs employed Polylactic acid-glycolic acid (PLGA) as the shell and cellulase and levofloxacin as the core were encapsulated via double ultrasonic emulsification. The synthesized CL@LEV-NPs are uniformly round with an average diameter of 196.2 ± 2.89 nm, and the zeta potential of －14.96 ± 5.35 mV, displaying high biosafety and sonodynamic properties. Then, BCG biofilms were treated with ultrasound and CL@LEV-NPs separately or together in vivo and in vitro. The results showed that ultrasound significantly promoted biofilms permeability and activated CL@LEV-NPs to generate large amounts of reactive oxygen species (ROS) in biofilms. The combined treatment with CL@LEV-NPs and US exhibited excellent anti-biofilm effect, which was mainly reflected in the significant reduction of biofilm biomass and viability, destruction of biofilm architecture in vitro and elimination of biofilms from in subcutaneous implant and remission of local inflammation in vivo. Our study suggested that US combined with composite drug-loaded nanoparticles would be a novel non-invasive, safe and effective treatment modality for the elimination of biofilm-associated infections caused by MTB.